2015
DOI: 10.1007/s10461-015-1049-3
|View full text |Cite
|
Sign up to set email alerts
|

“Manejar la Situacion”: Partner Notification, Partner Management, and Conceptual Frameworks for HIV/STI Control Among MSM in Peru

Abstract: Previous analyses of Partner Notification (PN) have addressed individual, interpersonal, social, and structural issues influencing PN outcomes but have paid less attention to the conceptual framework of PN itself. We conducted 18 individual interviews and 8 group discussions, in a two-stage qualitative research process, to explore the meanings and contexts of PN for sexually transmitted infections (STI) among men who have sex with men (MSM) and men who have sex with men and women (MSMW) in Lima, Peru. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 40 publications
(31 reference statements)
4
24
1
Order By: Relevance
“…These results are consistent with findings from our formative research, and reflect an absolute increase of 30% in the proportion of stable male partners notified and 15% among casual male partners (31). Synthesizing this data with our formative research findings, the positive effect of web-based-based systems on notification outcomes may be due to multiple factors, including the availability of an anonymous mechanism to notify partners of a potentially stigmatizing diagnosis, the ability to contact partners for whom only an e-mail address is known, and the opportunity to replicate existing methods of communication among young people already accustomed to communicating through online networks (30,43).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…These results are consistent with findings from our formative research, and reflect an absolute increase of 30% in the proportion of stable male partners notified and 15% among casual male partners (31). Synthesizing this data with our formative research findings, the positive effect of web-based-based systems on notification outcomes may be due to multiple factors, including the availability of an anonymous mechanism to notify partners of a potentially stigmatizing diagnosis, the ability to contact partners for whom only an e-mail address is known, and the opportunity to replicate existing methods of communication among young people already accustomed to communicating through online networks (30,43).…”
Section: Discussionsupporting
confidence: 53%
“…Our formative research with recently STI-diagnosed MSM from Lima, Peru found a high level of potential acceptability for web-based notification systems (30). In our study, availability of a website that could deliver anonymous notification messages was expected to significantly increase notification among men who would not expect to inform their partners under existing conditions (31).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…transactional partnerships or drug‐sharing contacts) and community norms across populations may further influence the acceptability and delivery of PNS. Formative evidence indicates that PNS may be acceptable to some members of key populations in LMIC , but may be challenging in others . Encouragingly, PNS approaches have also been successfully provided to gay, bisexual, and other men who have sex with men (MSM) and people who inject drugs (PWID) in several high‐income countries for many years and lessons learned from these programmes may inform scale‐up in LMICs.…”
Section: Pns For Key Populationsmentioning
confidence: 99%
“…Status communication is considered to be socially risky as once a positive status is disclosed, it could be told to others and the information is no longer completely controlled by the positive individual(11, 13). In the Peruvian context, discussion of HIV status remains highly stigmatized; it is a taboo topic of conversation among MSM, particularly if they just met(18). Additionally many HIV positive people do not know their serostatus due to infrequent HIV testing(19).…”
Section: Introductionmentioning
confidence: 99%